An Analysis of the Underlying Causes of Increase in Mexican Immigration to The United States After the 1970s - Özalp, Oğuz Kaan (2020)
Contrary to popular belief, the Mexican economy was in balance and stability in the 1950s. However, after announcing a fiscal expansion under the administration of Luis Echeverria in the 1970s, the Mexican government went under a pile of debt, which caused a change of atmosphere in Mexico by deepening civil, political, and economic problems, such as corruption, inequality, and class differences. Ultimately, the Mexicans who mostly lived in rural and poor areas faced the realities of these problems, which increased immigration to the United States. This trend started specifically after the 1970s. The 1970s of Mexico was a breaking point to accelerate the Mexican immigration, and consecutively, this has created a domino effect. Thus, this article examines the period after the 1970s to the 2010s, while indicating the underlying problems regarding the Mexican immigrants and Mexican society, mostly in rural and poor areas. The underlying problems such as North Atlantic Free Trade, failures of the Mexican political party, economic crises, inequality, corruption, and poverty constituted the primary drive of Mexican immigration to the United States in the 1980s and 1990s, and moreover, these problems did not cease after all. To create a concrete groundwork to analyze Mexican immigration, the article applies one of the migration theories called push- pull factors theory that contribute to the increase in Mexican immigration by mentioning the historical events, political discourses, and grassroots' problems. Consequently, the article aims to assert the importance of Mexican immigration to the United States as a case to be examined closely to understand Mexican immigrants' realities. Yaygın inanışın aksine, Meksika Ekonomisi 1950'lerde denge ve istikrar içindeydi. Ancak, 1970'lerde Luis Echeverria yönetimi altında bir mali genişleme politikası ve yapısal reformlar duyurduktan sonra Meksika hükümeti bir borç yığını altına girdi. Bu durum Meksika Hükümeti’nde, yolsuzluk, eşitsizlik ve sınıf farklılıkları gibi sivil, siyasi ...